The Focal Play Therapy: A Clinical Approach to Promote Child Health and Family Well-being - Chirico, Ilaria; Andrei, Federica; Salvatori, Paola; Malaguti, Irene; Trombini, Elena (Frontiers in Public Health, 2019)
Eating and evacuation disorders can cause serious health problems for children. Early recognition and early treatment require a multifactor intervention based on a collaborative relationship between pediatricians, psychotherapists and other health professionals. In this context the Focal Play Therapy (FPT) with children and parents is a psychodynamic model of intervention that improves parental ability to cope with child’s difficulties. Parental engagement in child interventions allows to understand child’s symptoms within family dynamics and to build an alliance with parents that represents a crucial variable of an effective psychological support for children and families. In the present study data were collected from 17 parental couples and their preschool children at two time points (1th and 6th FPT sessions) marking the first phase of this intervention. This phase was aimed to the assessment of child’s symptoms within family relationships and to the promotion of the alliance with parents. Families were in treatment at the Psychological Consultation Center for Children and Parents located at the Department of Psychology of the University of Bologna (Italy). This Center provides health assessment and intervention services to children and their families. We investigated the alliance from both parents and therapist points of view along with other parental and child outcome variables implied in clinical works with children and families. Alliance scores were obtained through the Working Alliance Inventory and the System for Observing Family Therapy Alliances, two measures used in individual and family settings respectively. Parenting stress and parent-child interactions were investigated using the Parenting Stress Index and the Emotional Availability Scales. Furthermore, paired t-tests were run to detect changes on parental and child variables. Findings advise that special attention should be paid to the building of an early alliance with parents. In this regard the FPT is specifically designed to promote the parent-therapist alliance in the context of child health and family well-being.